The feasibility of disseminating and implementing prolonged exposure therapy for survivors of trauma in South Africa: a mixed method pilot and feasibility study - Booysen, Duane Danny-Coe (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.